Driving Under Involuntary Distraction and Varied Perceptual Loads. (September 2016) - Hoekstra-Atwood, Liberty; Chen, Huei-Yen Winnie; Donmez, Birsen
Distracted driving compromises safety. One type of driver distraction often overlooked in experimental studies is involuntary engagement in driver distraction, which is related to an inability to suppress non-driving related information. The present work aims to discern how involuntary distraction affects drivers and whether perceptual load modulates involuntary distraction engagement. It was hypothesized, based on Load Theory, that drivers are worse at inhibiting irrelevant stimuli when driving under lower perceptual load. A simulator experiment manipulating distraction (involuntary vs. baseline) and perceptual load of the environment (high vs. low visual complexity) found that irrelevant stimuli degraded driving responses to lead vehicle braking events. Contrary to expectation, perceptual load did not affect involuntary distraction engagement.